The Determinants of Investment Rewards: Evidence for Selected Developed and Developing Countries - Tay, Bee-Hoong; Gan, Pei-Tha (International Journal of Economics and Financial Issues, 2016)
The empirical studies on investors' investment reward rarely focus on the performance of excess returns across the developing and developed countries: investment in the developing countries has higher risk thus requires higher return compared to developed countries. Therefore, study on investors' investment reward cannot rule out the role of the performance of excess returns simply because of data mining, complex data collection process and misspecification of the model. The objective of this study is to examine the underlying determinants of investors' investment reward on excess stock return such that provide better understanding on the fact that the developing countries has more risk compared to developed countries and the internal factors are important for investors in the investment decision making process. The findings of this study indicate that there is an equilibrium relationship between investors' investment reward and its determinants, namely, risk premium of market, firm size and book-to-market value. In addition, the internal factors are important to the investors in making investment decisions and the relationships of the underlying determinants are prevalent in the developing countries. This study suggests that risk premium of market, firm size and book-to-market value can serve as indicators of the investors' investment reward that provide better understanding that developing countries has more risk than developed countries. This study also suggests that the investors and policy makers should consider the role of the underlying determinants in the investors' investment decision making process. Keywords: excess stock return, risk premium of market, firm size, book-to-market value JEL Classifications: D46, G31